A Marginal(ized) Perspective on Translation History: Women and Translation in the Eighteenth Century - Agorni, Mirella (Meta, 2005)
AbstractTranslation was a prestigious activity in Britain in the Eighteenth Century, and the field was divided into two distinct areas: translation from the classics (focusing on Latin and Greek authors) which was a male-dominated territory, and translation from modern languages (French, German, Italian and Spanish) which was one of the few literary genres open to women. Yet, there were some significant exceptions in the area of the classics. I will analyze the case of Elizabeth Carter (1717-1806), the celebrated translator of Epictetus from the Greek, who developed a particularly original approach to translation, by adopting an ingenious form of proto-feminist collaboration with her friend Catherine Talbot (1721-70).